Resilensi Ekonomi Indonesia Ditengah Perang Dagang AS-Tiongkok : Analisis Geopolitik - Devis Heriyanto (CV Rewang Rencang, 2025)
The US-China trade war has disrupted the global economy, impacting Indonesia's import-export decline, rupiah exchange rate pressure, and financial market fluctuations. This study analyzes the impact by using a normative-empirical approach with trade and policy data. The findings show that Indonesia is stable through hedging strategies, neutral diplomacy, and diversification of trading partners. The study highlights the importance of an adaptive and resilient national trading system, supported by fiscal-monetary policy coordination. In addition to the evaluation, the study also provides strategic insights to strengthen Indonesia's economic resilience in the face of external shocks in an increasingly complex global trade environment.